Bioethanol production from lignocellulosic biomass (water hyacinth): A biofuel alternative - Krishnan, Santhana; Mohamad Faizal, Ahmad; Nur Azmira, Zainuddin; Mohd. Fadhil, Md. Din; Shahabaldin, Rezania; Shazwin, Mat Taib; Chelliapan, Shreeshivadasan; Mohd, Nasrullah; Zularisam, Abdul Wahid (Elsevier Inc., 2020)
Bioethanol is considered one of the most potential and attractive liquid fuels since the natural resources from fossil fuels become limited. Bioethanol, which can be derived from lignocellulosic biomass, is certainly drawing increasing attention due to the advantages of being readily available, low-cost, and environment-friendly. Therefore a study was performed on water hyacinth and water lettuce as potential sources of biofuel due to their abundance and ease of cultivation in nature. This chapter aims to investigate the potential of floating aquatic macrophytes to provide enough supply for bioethanol production. The feasibility of the biological pretreatment of water hyacinth and water lettuce using white rot fungi by monitoring lignin and hemicellulose biodegradation was studied. The potential of bioethanol production was determined by sugar consumption rate and percentage of fermentable sugar by Saccharomyces cerevisiae yeast. The experiment was fabricated with two tanks containing macrophytes, namely Eichhornia crassipes and Pistia stratiotes. The weight of both species was recorded for three consecutive days to monitor the optimum growth rate. Both species were pretreated with white rot fungi. The parameters involved were sugar content, lignin by Klasson method, and hemicellulose by Chesson method. The water hyacinth was fermented with different yeast concentrations in a stirred tank reactor and the dinitrosalicylic acid (DNS) method was used for sugar determination. The results showed that P. stratiotes have a higher growth rate than E. crassipes. However, E. crassipes was seen to be more feasible for lignin and hemicellulose biodegradation than P. stratiotes. The sugar consumption rate was found to be influenced by the yeast concentration, and the fermentable sugar concentration of the water hyacinth filtrate was recorded to be 70%.